1996
DOI: 10.1007/s004380050290
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the entomocidal fragment of Spodoptera-specific Bacillus thuringiensis toxin CryIC

Abstract: Insecticidal CryI protoxins of Bacillus thuringiensis are activated by proteolysis in the midgut of insects. A conservation of proteolytic cleavage sites in the CryI proteins facilitates the expression of active toxins in transgenic plants to obtain protection from various insects. However, the engineering of CryIC toxins has, thus far, failed to yield applicable resistance to armyworms of Spodoptera species representing common insect pests worldwide. To improve the production of recombinant CryIC toxins, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
2
7
0
1
Order By: Relevance
“…However, this report contained no data on the relative toxicity of Cry1C-t or full-length Cry1C molecules to S. littoralis. The sequence of the Cry1C-t used in the present study was identical to the sequence of the Cry1C-t described previously (19). Here, it is shown that Cry1C-t produced in B. thuringiensis is also toxic to larvae of the beet armyworm, S. exigua, although the toxicity of the truncated protein was 7-to 12.6-fold less than that of the full-length Cry1C (Table 3).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…However, this report contained no data on the relative toxicity of Cry1C-t or full-length Cry1C molecules to S. littoralis. The sequence of the Cry1C-t used in the present study was identical to the sequence of the Cry1C-t described previously (19). Here, it is shown that Cry1C-t produced in B. thuringiensis is also toxic to larvae of the beet armyworm, S. exigua, although the toxicity of the truncated protein was 7-to 12.6-fold less than that of the full-length Cry1C (Table 3).…”
Section: Discussionsupporting
confidence: 76%
“…5), which were degraded to 31-kDa peptides (Fig. 3B), were possibly the translation products resulting from a second in-frame ATG codon, as noted previously (19).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Proteolytic activation of Cry1 protoxins involves the removal of peptide sequences from both N and C termini. The observations that a mutant toxin in which Nterminal cleavage is prevented has reduced toxicity (4) and that N-terminally truncated toxins are toxic to Escherichia coli expression hosts (4,9) suggest that N-terminal cleavage may be an important part of the toxic mechanism.…”
mentioning
confidence: 99%